2009
DOI: 10.1002/cne.21942
|View full text |Cite
|
Sign up to set email alerts
|

Neural organization of first optic neuropils in the littoral crab Hemigrapsus oregonensis and the semiterrestrial species Chasmagnathus granulatus

Abstract: Crustaceans are among the most extensively distributed arthropods, occupying many ecologies and manifesting a great variety of compound eye optics; but in comparison with insects, relatively little is known about the organization and neuronal morphologies of their underlying optic neuropils. Most studies, which have been limited to descriptions of the first neuropil - the lamina - suggest that different species have approximately comparable cell types. However, such studies have been limited with regard to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 48 publications
5
67
0
Order By: Relevance
“…A more complete picture is emerging from recent work on the crab Chasmagnathus. This includes a thorough histological study based on silver staining of neurones (Sztarker et al, 2005;Sztarker et al, 2009) and a detailed analysis of the different properties of lobular neurones involved in escape responses to looming stimuli (Berón de Astrada and Tomsic, 2002;Medan et al, 2007;Oliva et al, 2007;Sztarker and Tomsic, 2008), several of which show a form of learning related to habituation (Tomsic et al, 2003). Yet none of this work refers to the term 'optic flow', nor have stimuli appropriate for the identification of neurones tuned to optic flow been used.…”
Section: Identity Of the Populations Of Medulla And Lobula Neurones Wmentioning
confidence: 99%
See 2 more Smart Citations
“…A more complete picture is emerging from recent work on the crab Chasmagnathus. This includes a thorough histological study based on silver staining of neurones (Sztarker et al, 2005;Sztarker et al, 2009) and a detailed analysis of the different properties of lobular neurones involved in escape responses to looming stimuli (Berón de Astrada and Tomsic, 2002;Medan et al, 2007;Oliva et al, 2007;Sztarker and Tomsic, 2008), several of which show a form of learning related to habituation (Tomsic et al, 2003). Yet none of this work refers to the term 'optic flow', nor have stimuli appropriate for the identification of neurones tuned to optic flow been used.…”
Section: Identity Of the Populations Of Medulla And Lobula Neurones Wmentioning
confidence: 99%
“…Unlike Chasmagnathus lobula neurones, those of C. maenas do not show strong habituation, which is an important feature of neurones that elicit escape. Indeed, there is good evidence that, although different crab species (and, to a lesser extent, different decapods) do have homologous neurones, such neurones may become specialised for different functions according to the lifestyle of the species (Sztarker et al, 2005;Sztarker et al, 2009). It is also worth pointing out that a well-studied looming neurone in locusts, the lobula giant movement detector (LGMD) is not directionally selective (Krapp and Gabbiani, 2005); therefore, looming detection and optic flow processing are not necessarily linked.…”
Section: B G Horseman M W S Macauley and W J P Barnesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial investigation into the optic neuropils (Kleinlogel et al, 2003, Kleinlogel and Marshall, 2005, Thoen et al, 2017 revealed they follow a similar layout to what is seen in other crustaceans, but that the midband pathway is distinctly visible throughout the three first optic lobes. The lamina ganglionaris is the best studied optic neuropil in crustaceans (Hamori and Horridge, 1966, Nassel, 1975, Nassel and Waterman, 1977, Strausfeld and Nassel, 1981, Sztarker et al, 2009. It is the first optic neuropil, below the retina, and it is composed of cartridges, each of which contains the photoreceptor axons and terminals of the R1-8 cells from a single ommatidium Marshall, 2005, Thoen, 2014) (Fig.…”
Section: The Optic Neuropils Of Stomatopodsmentioning
confidence: 99%
“…In rows 5 and 6 of the midband the lvfs are mostly smooth compared to those of rows 1-4 which have many dendrites innervating both layers of the lamina. (Nassel, 1977, Nassel and Waterman, 1977, S. et al, 1977, Strausfeld and Nassel, 1981, Sztarker et al, 2009). These are identified by the location of their cell body (in either the proximal (PML) or distal (DML) monopolar cell layer), the location of their dendrites in the external plexiform layers and whether they are contained within a single cartridge or extend into adjacent ones (Fig 5.1D and E).…”
Section: Lamina General Morphologymentioning
confidence: 99%